If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 39 + -5x = 13x + 19 Reorder the terms: 39 + -5x = 19 + 13x Solving 39 + -5x = 19 + 13x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-13x' to each side of the equation. 39 + -5x + -13x = 19 + 13x + -13x Combine like terms: -5x + -13x = -18x 39 + -18x = 19 + 13x + -13x Combine like terms: 13x + -13x = 0 39 + -18x = 19 + 0 39 + -18x = 19 Add '-39' to each side of the equation. 39 + -39 + -18x = 19 + -39 Combine like terms: 39 + -39 = 0 0 + -18x = 19 + -39 -18x = 19 + -39 Combine like terms: 19 + -39 = -20 -18x = -20 Divide each side by '-18'. x = 1.111111111 Simplifying x = 1.111111111
| -a^2+20a-60=0 | | 25x^2+10x+1=7 | | 16x^2-8x+1=11 | | x=4y*1.2 | | x^2-6x+9=9 | | 34=10+4q | | 5s^2+23s+24=0 | | -2X^2+14X+196=0 | | a+a=a | | 2q+2=-12 | | 4x^2+28X=240 | | 2x-4=x+9 | | (x-2)(3x+8)=0 | | ln(x)+ln(x-6)=ln(16) | | (50-4y)+(25-2x)=100 | | -36+2w=8w+w | | 7X-8X-9X+2+3+17X=12 | | 111111111111111111111(a)= | | -x-4=16 | | -10=6+2c | | 5.25+x=3.75 | | b+5=-13 | | x-(x*0.2)=9.6 | | 23=x-17 | | n-2=-5 | | 3+4(2x-1)-2=5-2(x-1) | | -6+12+-9= | | 12+5.1+3.7= | | 6p+12=2p-4 | | 135.7*10= | | 18-5x(2+3)= | | 12x^2+13x+14=0 |